2023
DOI: 10.1007/s40265-023-01858-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Amyloid Monoclonal Antibodies are Transformative Treatments that Redefine Alzheimer's Disease Therapeutics

Abstract: Two anti-amyloid monoclonal antibodies (MABs)-lecanemab (Leqembi ® ) and aducanumab (Aduhelm ® )-have been approved in the USA for the treatment of Alzheimer's disease (AD). Anti-amyloid monoclonal antibodies are the first disease-modifying therapies for AD that achieve slowing of clinical decline by intervening in the basic biological processes of the disease. These are breakthrough agents that can slow the inevitable progression of AD into more severe cognitive impairment. The results of trials of anti-amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…While the insoluble amyloid aggregates are considered a disease hallmark, soluble oligomeric species are however better correlated with memory impairment and AD progression. 33,38 The recent FDA approval of Lecanemab and Aducanumab, 13 antibodies which target Ab aggregates in the brain, has resulted in renewed interest in the development of small-molecules that target this disease pathway. 14 AD is also associated with an increase in reactive oxygen species (ROS), with early pathological changes indicating oxidative damage in the brain.…”
Section: Tim Storrmentioning
confidence: 99%
See 1 more Smart Citation
“…While the insoluble amyloid aggregates are considered a disease hallmark, soluble oligomeric species are however better correlated with memory impairment and AD progression. 33,38 The recent FDA approval of Lecanemab and Aducanumab, 13 antibodies which target Ab aggregates in the brain, has resulted in renewed interest in the development of small-molecules that target this disease pathway. 14 AD is also associated with an increase in reactive oxygen species (ROS), with early pathological changes indicating oxidative damage in the brain.…”
Section: Tim Storrmentioning
confidence: 99%
“…The recent FDA approval of antibodies targeting this pathway, has renewed interest in the development of small molecule agents that modulate Ab aggregation. 13 In addition, new work has shown that protein aggregates (Ab and tau) increase levels of neuron-specific maternally expressed gene 3 (MEG3) which induces necroptosis in human neurons in vitro. 133 MEG3 is also upregulated in AD patients thus providing a link to the neuronal toxicity of these aggregates.…”
Section: Summary On Multifunctional Agents Targeting the Ab Peptidementioning
confidence: 99%
“…The monoclonal antibodies aducanumab (Biogen), gantenerumab (Roche), crenezumab (Roche), sola- nezumab (Eli Lilly), lecanemab (Eisai, Biogen), and donanemab (Eli Lilly) have been examined in various phase III studies. Overviews of these studies are provided in [27][28][29][30]. After the EMERGE and ENGAGE studies by Biogen were terminated due to a lack of efficacy, an analysis of the final examinations with a treatment duration that was 6 months longer on average showed that patients treated for a longer time with higher doses of aducanumab experienced a significant delay in cognitive decline and a decrease in amyloid deposits on amyloid PET.…”
Section: Treatment Of Alzheimer's Diseasementioning
confidence: 99%
“…The process of amyloid-β protein (Aβ) fibrillogenesis is responsible for triggering a cascade of physiological events that contribute directly to the initiation and progression of AD . This hypothesis led to the FDA approval of the anti-amyloid antibody Aduhelm (aducanumab-avwa) to treat mild to moderate stages of AD and more recently Leqembi (lecanemab-irmb), the second in a new category of medications . Nevertheless, disease-modifying therapies by small molecules are still considered quite challenging.…”
mentioning
confidence: 99%
“…3 This hypothesis led to the FDA approval of the anti-amyloid antibody Aduhelm (aducanumab-avwa) to treat mild to moderate stages of AD and more recently Leqembi (lecanemab-irmb), the second in a new category of medications. 4 Nevertheless, disease-modifying therapies by small molecules are still considered quite challenging. Tau is a microtubule-associated protein mostly found in neuronal axons in the central nervous system.…”
mentioning
confidence: 99%